2019
DOI: 10.15548/jk.v9i2.303
|View full text |Cite
|
Sign up to set email alerts
|

Klèbun Babine’: Praktik, Gaya Kepemimpinan dan Faktor Pendorong Keberhasilan Memimpin Pemerintah Desa

Abstract: The village women leader (Klèbun Babine') in Madura is not fully considered. They were merely a symbol and administrative officer. While the policy determinant is on the husband or family of the male party. In contrast, the case study of women Head Village chief Ponteh successfully run the village government without the influence of the husband or family from the male side. The leadership of Klèbun Babine' is not inferior to the village head led by men. The case study revealed the leadership practices, leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
3
1
Order By: Relevance
“…This study did not find a phenomenon such as in the research of Karim (2007) or Satriyati (2009) and Sabariman (2019), who found that female Klebun was able to carry out her duties using her own distinctive style and take on leadership. Female Klebun continue to fulfil her duties only within the scope and purview of obeying an obligation given to her by her husband.…”
Section: Female Klebun In Fulfilling the Leadership Duties Of A Village Chiefcontrasting
confidence: 63%
See 1 more Smart Citation
“…This study did not find a phenomenon such as in the research of Karim (2007) or Satriyati (2009) and Sabariman (2019), who found that female Klebun was able to carry out her duties using her own distinctive style and take on leadership. Female Klebun continue to fulfil her duties only within the scope and purview of obeying an obligation given to her by her husband.…”
Section: Female Klebun In Fulfilling the Leadership Duties Of A Village Chiefcontrasting
confidence: 63%
“…On the other hand, independent and creative female Klebun was found in Karim's (2007) and Satriyati (2009) research. In addition, Sabariman (2019) found that female Klebun who can lead the village of Ponteh, Galis District, Pamekasan Regency successfully have a certain leadership style. Success is measured by the ability to complete administrative tasks and other tasks.…”
Section: Introductionmentioning
confidence: 99%
“…Several works of literature that examine women's leadership in regions and villages have been conducted, such as the success of women's leadership in the village, namely the female village head who succeeded in making the village selfsufficient (Desa Swakarya) (Utaminingsih et al, 2020). In addition, other studies explain how the success of women leaders cannot be separated from the existence of equal and fair gender government policies in society (Sabariman et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The same thing is also explained when women, in order to carry out their leadership, tend to pay attention to governance and can adjust to the situation when carrying out interactions. They communicate and coordinate while performing their leadership duties (Sabariman et al, 2019). Interestingly, women have a point of view in how they behave when a problem occurs in the community by responding like a mother to her child (Utaminingsih et al, 2020).…”
Section: Introductionmentioning
confidence: 99%